TELAAH HISTORIS PONDOK PESANTREN SEBAGAI LEMBAGA PENDIDIKAN ISLAM - Wakia, Nurul; Yahdi, Muhammad (IAIN Bone, 2024)
AbstractThis research is motivated by the nature and existence of Islamic boarding schools as educational institutions that are deeply rooted (indigenous) in Indonesian Muslim society, in its development Islamic boarding schools are able to maintain and preserve their sustainability (survival system). The purpose of this writing is to examine the background of Islamic education, especially in Indonesia and to examine the significance of Islamic boarding schools as one of the Islamic educational institutions. Document studies in the form of soft copies and written documents were used to collect data for this research which were then analyzed qualitatively. Based on the results of the study, the existence of Islamic boarding schools in Indonesia is increasingly well-known and increasingly varied. Islamic boarding schools are Islamic educational institutions that have an important role in the midst of society, covering at least three aspects, namely religious functions, social functions, and educational functions.Â Keywords: Historical Review, Islamic Boarding School, Islamic EducationÂ